CLONAGEM, EXPRESSÃO E CARACTERIZAÇÃO DA NUCLEOPROTEÍNA RECOMBINANTE DO VÍRUS DA BRONQUITE INFECCIOSA EM ESCHERICHIA COLI E EM PICHIA PASTORIS - Gibertoni, A.m. [UNESP] (2020)
The nucleocapsid protein (N) gene (1,230 bp) of the M41 strain of infectious bronchitis virus (IBV) was amplified by reverse transcriptase-polymerase chain reaction (RT-PCR), and cloned in two systems; pET28a Escherichia coli and pFLD Pichia pastoris. The recombinant expression constructs (pET28a-N or pFLD-N) were identified by PCR and sequencing analysis. The transformant clones of BL21 strain of E. coli or GS115 of P. pastoris were submitted to appropriate inducting protocols. Expression of histidine-tagged fusion N proteins with a molecular mass of 54 kDa was determined by SDS-PAGE and Western blotting analysis, confirming that both recombinant N proteins were comparable in size and antigenicity to native IBV N protein. The E. coli system overexpressed the recombinant N protein, while the P. pastoris system produced a low yield of this recombinant protein. The bacteria expressed N protein was purified by chromatography on nickel-sepharose resin. These results indicated that the pET28a E. coli expression system is more effective to generate N recombinant protein for using as an antigen to detect anti-IBV antibodies in immuno-assays for this viral infection.